2016
DOI: 10.1371/journal.pone.0153807
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and Vomiting following Balanced Xenon Anesthesia Compared to Sevoflurane: A Post-Hoc Explorative Analysis of a Randomized Controlled Trial

Abstract: ObjectiveLike other inhalational anesthetics xenon seems to be associated with post-operative nausea and vomiting (PONV). We assessed nausea incidence following balanced xenon anesthesia compared to sevoflurane, and dexamethasone for its prophylaxis in a randomized controlled trial with post-hoc explorative analysis.Methods220 subjects with elevated PONV risk (Apfel score ≥2) undergoing elective abdominal surgery were randomized to receive xenon or sevoflurane anesthesia and dexamethasone or placebo after writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…However, the decrease in HR did not result in a decrease of patients’ MAP, especially when a high concentration of sufentanil was administrated. It implies the hemodynamic safety range of sufentanil is large, which is consistent with the results of Fechner and his colleagues [ 31 ]. Our study did show that the use of sufentanil at a large dose results in a delay of anaesthesia recovery (Table 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the decrease in HR did not result in a decrease of patients’ MAP, especially when a high concentration of sufentanil was administrated. It implies the hemodynamic safety range of sufentanil is large, which is consistent with the results of Fechner and his colleagues [ 31 ]. Our study did show that the use of sufentanil at a large dose results in a delay of anaesthesia recovery (Table 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the decrease in HR did not result in a decrease of patients' MAP, especially when high concentration of sufentanil was administrated. It implies the safety range of sufentanil is large, which is consistent with the results of Fechner and his colleagues [32] . Nevertheless, our study showed the use of sufentanil at a large dose results in the delay of anaesthesia recovery (table1).…”
Section: Discussionsupporting
confidence: 90%
“…The anomalous electrophysiology of the NMDA antagonistic anesthetics may be attributed to a number of factors. Firstly, investigations of gaseous N 2 O and Xe when compared to intravenous ketamine, are limited to a small number of studies potentially due to the unclear clinical utility of Xe as well as the widely reported association with post-operative nausea and vomiting 21-23 , and pronounced dissociative effects. In addition, dosage differences across studies ranging from subanesthetic to anesthetic levels 14,15,19,20,24 and the common practice inclusion of concomitant agents 17,25 , encumber the ability to draw conclusive findings.…”
Section: Introductionmentioning
confidence: 99%